A Top-Level Design and Deployment Practice for Mobile Internet Smart Pipe - Jin Ding (Dianxin kexue)
In the mobile internet era, along with the rapid development of smart phones and the variation of user requirements, telecommunication operators meets more and more new challenges, for instance, network congestion happens more frequently, network resources are unfairly distributed, and revenue does not grow in step with network flows. Based on the PCC architecture, a scheme of top-level design and deployment practice for mobile internet smart pipe was proposed. Moreover the deployment practice has achieved good results, which would build solid foundation for the implementation of traffic flow based market operation.